Assessing the possibility of winning a WTO dispute before being involved - Nikolai Klishch; Alexander Larionov (Journal of Economics, Finance and Administrative Science, 2022)
Purpose - This article focuses on whether there is a chance to win a World Trade Organization (WTO) trade dispute at the consultation stage. The study suggests an approach to resolving trade disputes on a bilateral level before involving formal WTO resolution procedures. Design/methodology/approach - The model describes the determinants of the probability of winning a trade dispute. The econometric model estimates two different groups of factors available during the consultation period - macroeconomic factors and the institutional features of the trade dispute, such as the number of third parties. The data includes WTO trade disputes from 1995 to 2014. Findings - The suggested model predicts the result of trade disputes with a probability of 76.64%. The research proves that institutional factors such as the number of third parties and the subject of the trade dispute influence the probability of winning. Practical implications - The results of the study help predict the probability of winning a trade dispute at the consultation stage so that countries can decide whether to pursue a trade dispute. Originality/value - The research presents several new hypotheses on the results of trade disputes. The authors show that the higher the number of countries involved, the higher the chance of the complainant winning and that if major parties such as the US or the European Union (EU) are involved as third parties, the chance of the complainant winning increases.
Keywords: 330; WTO; Trade disputes; Dispute settlement; Tariffs; Macroeconomic factors; Trade policy